Motivation and Non-Physical Environment in Improving Employee Performance - Vilma Sevilla; Anita Novialumi (Economic: Journal Economic and Business, 2025)
This study uses a quantitative approach to analyze the influence of the non-physical work environment and work motivation on employee performance at Rai Fitness Bali. A total of 53 employees became respondents in this study. Based on the results of the regression analysis, it is known that the non-physical work environment and work motivation have a significant effect on employee performance, both partially and simultaneously. The results of the F test indicate that both variables jointly influence employee performance, while the t test shows a positive effect with a significance value of less than 0.05. The R² value of 0.748 indicates that the non-physical work environment and work motivation are able to explain 74.8% of the variation in employee performance, while the rest is influenced by other factors outside the research model. Thus, this study confirms that companies need to strengthen employee work motivation and create a conducive non-physical work environment to encourage optimal performance improvement.